Proses Pemurnian Asap Cair dan Simulasi Akumulasi Kadar Benzopyrene pada Proses Perendaman Ikan - Purnama Darmadji; Huda Triyudiana (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2006)
This research was aimed to determine the influence ofpurification on the concentration of tar and benzopyrene of prifiede liquid smoke and to simulate the concentration of benzopyerene during deeping of fish in the purified liquid smoke. The purification was done using several methods included sedimentation, filtration, adsorbtion, and redistillation at up to 100 C, 125 C, 150 C, and 200 C. The results of the research showed that during sedimentation, filtration, adsorbtion, redistillation at up to 100, 125, 150 and 200 C the concentration of tar was 1.24%, 1.19%, 0.45%, 0.44%, 0.59%, 0.72% and 1.20% respectivelly and the concentration of benzopyrene was 305 ppm, 110 ppm 0.196 ppm, 0.196 ppm, 0.196 ppm and 0.196 respectively. The stimulation of the dipping offish in redistillate liquid smoke showed that the fish dipped in 5% solution of redistillate liquid smoke for 15 minutes to 120 minutes the concentration of benzopyrene in fish was less than 1 ppb. That was indicate that redistilled liquid smoke was safe for dipping offish.